Penapisan Bakteri Penghambat Fusarium yang Diisolasi dari Cairan Kantung Semar (Nepenthes sp.) - Siti Meliah; Annisa Wahyu Hardiyanti; Ni’ma Haida; Gita Azizah Putri; Erny Qurotul Ainy (Jurnal Ilmu Pertanian Indonesia, 2020)
The genus Fusarium sp. is a pathogenic fungal for many cultivated plants. The bacteria isolated from monkey cup (Nepenthes sp.) fluid possess the ability to produce hydrolytic enzyme, such as chitinase which can be utilized to inhibit the growth of mycelia of pathogenic fungi. The aims of this study are to isolate bacteria from monkey cup liquid, to test their abilities to produce protease, chitinase, and cellulase, as well as their abilities to inhibit Fusarium. The bacteria were isolated using serial dilution method on Reasoner’s 2A agar medium. Enzymatic activities of bacterial isolates were determined by inoculating them on tested medium supplemented with casein protein, chitin, and cellulose, whereas their antifungal activities were assayed using a direct confrontation method between tested bacterial isolates and pathogenic fungal on Malt Extract Agar medium. Molecular identification of bacteria with antifungal activity was performed by analyzing the 16S rRNA gene sequences. Isolation process of bacteria from monkey cup fluid resulted in 99 bacterial isolates with the ability to produce either protease, chitinase, and/or cellulose enzymes. A total of 37 bacterial isolates were capable of producing at least two hydrolytic enzymes. Antifungal assay of those bacteria showed that as many as 25 isolates have the ability to inhibit the growth of Fusarium sp. Based on the analysis of 16S rRNA gene sequences revealed that those isolates were closely related to three Burkholderia species, namely B. arboris, B. contaminans, and B. rijonensis. Keywords: antifungal, Burkholderia, chitinase, cellulaseN, epenthes, protease